Basic laws of the intensive way of production development - Bahaliubskaya-Siniakova, Katsiaryna S. (Journal of the Belarusian State University. Economics, 2021)
The paper examines the way of enterprise’s production development based on the intensification of production. Intensification involves improving the production process through more efficient use of the factors of production available to the organisation. The analysis of the best options for doing business is based on the economic and mathematical model of firm’s revenue, which includes such parameters as the coefficient of price reduction due to the introduction of innovations into the production process, the coefficient of price elasticity of demand and the rate of price growth, which depends on the inflation rate. The results of the study of this model determine the conditions of improving the production process in order to obtain greater benefits for the entrepreneur. Based on these conditions, the fundamental principles and patterns of the intensive way of production development are identified.
Keywords: revenue; way of production development; intensification of production; revenue growth law; entrepreneur’s benefit